Impact of Foreign Investment on Economic Growth in OECD’s Members: A Panel Data Model, 1977-2017 - Aali-Bujari, AlÃ; Venegas-MartÃnez, Francisco; GÃ³mez-RodrÃguez, TomÃ¡s (Journal of Reviews on Global Economics, 2019)
Motivation: This paper is aimed at analyzing the impact of foreign investment (FI) on economic growth (EG) in Australia, Canada, Germany, Spain, Finland, France, United Kingdom, Greece, Italy, Japan, Republic of Korea, Mexico, Netherlands, Norway, New Zealand, and USA. Novelty: The research is: 1) concentrated in countries belonging to the OECD; 2) based on a greater number of countries, variables and periods; and 3) addressed to correcting multicollinearity and autocorrelation of data. Methodology: A Granger causality analysis is carried out and both static and dynamic panel data models are estimated. Data and Empirical Analysis: Data is obtained from World Bank for the period 1977-2017. The causality of Granger reveals that during the first 10 years there is a unidirectional relationship from FI toward EG. In the following 15 years, there is empirical evidence of a bidirectional causal relationship. Moreover, during the whole period of study, 7 years have a unidirectional causality from EG toward FI. Finally, estimates of both static and dynamic panel data models show that FI has a positive impact on EG in all the studied economies. Policy Considerations: A set of recommendations for policy designers and decision makers is provided to build the appropriate instruments and incentives to encourage the attraction of FI to boost EG and, therefore, to enhance social welfare.